Research on Detecting Thickness of High Temperature Float Glass by Laser Trigonometry Measurement of CCD Sensor (Journal of Fiber Bioengineering and Informatics, 2015)
It is very important to use the detection technology of float glass thickness in glass production. In the\rprocess of detecting glass thickness on line, we adopt laser trigonometry displacement detection theory.\rDirecting at detection system theory in the high-temperature state, the paper does a further analysis.\rThe paper analyzes the theory and experimental results by using the CDD detection method. The\rresearch improves the precision and stability of the detection, increases the glass production quality and\rcuts down the energy consumption and production cost.
Keywords: CCD; Trigonometry; High Temperature; Detection